Effect of Health Education Programme on the Knowledge regarding Hand Washing and Immunization in the Disadvantaged Community of Eastern Nepal - Karn, Rajiv; Bhandari, Buna; Shrestha, Archana; Dhabadi, Bashav Raj (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 18-23 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8800